Experiences of Indonesian Adolescents Losing Parents Due to COVID-19: a Phenomenological Study - Novianti, Evin; Mustikasari, Mustikasari (IJNP (Indonesian Journal of Nursing Practices), 2023)
Background: Adolescents losing their parents is the worst event they experience during the COVID-19 pandemic. Adolescents raise a traumatic response after a loss occurs.Objective: This study aims to explore the description of the condition of adolescents in dealing with the loss of parents due to COVID-19.Methods: Qualitative research design with a phenomenological approach. The number of participants is 12 people with the criteria of youth aged 10-19 years consisting of men and women who have lost their parents due to COVID-19. Interview data were processed using the Colaizzi technique.Results: Four themes through the theme analysis, namely adolescents are not ready to face sudden loss, adolescents experience suffering due to the loss of parents, adolescents find it difficult to go through the loss process, and changes occur in adolescents due to the loss of parents.Conclusion: The findings of this study show that the sudden loss of parents due to COVID-19 harms adolescent mental health. As a result, mental health nurses in the community need to detect adolescents early for signs of stress and anxiety due to the loss of parents and take steps to strengthen adolescents' self-defense after loss.